Numerical Analysis of CNC-Grinding Process based on Complex Surface of Aviation Face Gear - Wang Yanzhong; Zhao Hongpu; Lan Zhou; Hou Liangwei; Zhong Yang; Lv Qingjun (Jixie chuandong)
The precision grinding technology of face gear is a key difficulty to its further development. According to study the characteristics of the special grinding generative movement of face gear,the numerical analysis of face gear grinding process is studied based on the software of ABAQUS and taking the residual stress as parameter index. The reliability of grinding simulation is determined through the analysis of simulation process.According to the results of the orthogonal analysis and rule explores,the influence law of the grinding velocity,feed velocity,cutting depth and grain size on the residual stress is obtained. The targeted results have high reliability,and the theoretical basis of grinding wheel selection and grinding parameters chosen for face gear grinding is established.